Intensified Adjuvant IFADIC Chemotherapy for Adult Soft Tissue Sarcoma: A Prospective Randomized Feasibility Trial. (2000) - Brodowicz, Thomas; Schwameis, Eva; Widder, Joachim; Amann, Gabriele; Wiltschke, Christoph; Dominkus, Martin; Windhager, Reinhard; Ritschl, Peter; Pötter, Richard; Kotz, Rainer; Zielinski, Christoph C.
Abstract : Purpose. The present prospective randomized adjuvant trial was carried out to compare the toxicity, feasibility and efficacy of augmented chemotherapy added to hyperfractionated accelerated radiotherapy after wide or marginal resection of grade 2 and grade 3 soft tissue sarcoma (STS). Patients and methods. Fifty-nine patients underwent primary surgery by wide or marginal excision and were subsequently randomized to receive radiotherapy alone or under the addition of six courses of ifosfamide (1500 mg/m 2, days 1–4), dacarbazine (DTIC) (200 mg/m 2, days 1–4) and doxorubicin (25 mg/m 2, days 1–2) administered in 14-day-intervals supported by granulocyte-colony stimulating factor (30 ×10 6 IU/day, s.c.) on days 5–13. According to the randomization protocol, 28 patients received radiotherapy only, whereas 31 patients were treated with additional chemotherapy. Results. The relative ifosfamide–doxorubicin–DTIC (IFADIC) dose intensity achieved was 93%. After a mean observation period of 41±19.7 months (range, 8.1–84 months), 16 patients (57%) in the control group versus 24 patients (77%) in the chemotherapy group were free of disease (p>0.05).Within the control group, tumor relapses occurred in 12 patients (43%;six patients with distant metastases, two with local relapse, four with both) versus seven patients (23%; five patients with distant metastases, one with local recurrence, one with both) from the chemotherapy group. Relapse-free survival (RFS) ( p =0.1), time to local failure (TLF) ( p =0.09), time to distant failure (TDF) ( p =0.17) as well as overall survival (OS) ( p =0.4) did not differ significantly between the two treatment groups. Treatment-related toxicity was generally mild in both treatment arms. Conclusion. We conclude that the safety profile of intensified IFADIC added to radiotherapy was manageable and tolerable in the current setting. Inclusion of intensified IFADIC was not translated into a significant benefit concerning OS, RFS, TLF andTDF as compared with radiotherapy only, although a potential benefit of chemotherapy for grade 3 STS patients needs to be validated in prospective randomized trials including larger patient numbers.